Translation Shift In The English- Indonesian Translation of The Old Man And The Sea Novel - Kusuma Wardani, Aida; Ayu Made Puspani, Ida; Qomariana, Yana (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study examines the translation shift phenomenon and covers equivalence in literary translation. The main objective of this study is to identify the translation shifts found in the English and Indonesian texts. The first data of this research is from the original book The Old Man and the Sea by Hemingway and its translated version by Damono. This research uses a qualitative research approach with a descriptive analysis method. The data is collected through document analysis by comparing the source text with its translation in Indonesian. The analytical framework is based on Catford's (1965) translation shift theory, which categorizes shifts into level shifts and category shifts. In addition, this study utilizes Nida and Taber's (1969) equivalence theory. The analysis shows that there has been translation shifts in the novel The Old Man and the Sea and its translation. In general, two types of translation shifts are identified in the text. First is a level shift, in which language elements move from one grammatical level to another between the source language and the target language. The second is category shift, which includes structure, class, unit, and intra-system shift. These shifts reflect the different linguistic systems between the source language (English) and the target language (Indonesian). Additionally, two translation equivalents were found, the first a formal equivalent and the second a dynamic equivalent, which the translator used to produce natural and acceptable equivalents in the cultural and grammatical context of the target language.